Pemberdayaan Taruna Pelayaran melalui Workshop Anti Korupsi Maritim: Strategi Membangun Pelaut Berintegritas untuk Menghadapi Tantangan Global - Dian Erliyani; Slamet Riyadi (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
This activity aims to improve the knowledge, awareness, and anti-corruption competency of final-year maritime cadets from all APPI member universities regarding international and national maritime anti-corruption regulations, further strengthening the ethical decision-making abilities of maritime cadets in dealing with corrupt situations in ports and on ships through a simulation approach based on real cases. This activity is designed as a participatory educational workshop with an active and experiential learning approach to adult learning (andragogy), which allows the implementation team to simultaneously collect scientific data on the effectiveness of workshop interventions in increasing participants' anti-corruption knowledge and awareness. The activity is carried out through three main stages that are systematically structured, namely the preparation stage, the implementation stage, and the evaluation and follow-up stage. The results of the activity confirm the effectiveness of the participatory workshop approach based on real case simulations (experiential learning) in significantly increasing knowledge and changing anti-corruption attitudes of maritime cadets in a relatively short duration. Furthermore, cadets have a stronger stock of knowledge, awareness, and moral commitment to deal with corrupt situations in the work environment. It is concluded that the participatory workshop approach based on real-life case simulations is an effective, efficient, and replicable strategy in empowering the next generation of Indonesian seafarers to face the challenges of corruption in the global maritime industry.